2010
DOI: 10.1017/s0031182010001095
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gene expression patterns amongLeishmania braziliensisclinical isolates showing a differentin vitrosusceptibility to pentavalent antimony

Abstract: Evaluation of Leishmania drug susceptibility depends on in vitro Sb(V) susceptibility assays, which are labour-intensive and may give a biased view of the true parasite resistance. Molecular markers are urgently needed to improve and simplify the monitoring of Sb(V)-resistance. We analysed here the gene expression profile of 21 L. braziliensis clinical isolates in vitro defined as Sb(V)-resistant and -sensitive, in order to identify potential resistance markers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 33 publications
4
27
0
Order By: Relevance
“…Overall, our results indicate that molecular resistance in Leishmania is multifactorial. These findings are generally in accordance with several multigene studies focused on other areas where leishmaniasis is endemic (45,46). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, our results indicate that molecular resistance in Leishmania is multifactorial. These findings are generally in accordance with several multigene studies focused on other areas where leishmaniasis is endemic (45,46). …”
Section: Discussionsupporting
confidence: 92%
“…Additionally, neither amplification nor overexpression of TRYR, HSP83, SKCRP, and MDR1 was observed, although these genes have displayed differential gene numbers or mRNA levels between sensitive and resistant parasites in other studies (19,45,46,49,50). These negative results could be due to the geographical particularities of mechanisms of resistance in western Mediterranean countries.…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, the emergence of multiple origins of drug resistance in this population together with different genomic signatures encountered among antimonial-resistant parasites is compatible with a pleomorphic response of L. donovani. This is supported by previous studies targeting specific genes and pointing out different patterns of overexpression in antimonial-resistant parasites (Adaui et al 2011).…”
Section: Discussionsupporting
confidence: 80%
“…Data from in vitroselected antimony-resistant parasites revealed that one or more simultaneously present mechanisms including loss in metal reduction, overexpression of thiol biosynthetic enzymes [γ-glutamylcysteine synthetase (γ-GCS), ornithine decaboxylase (ODC) and trypanothione reductase (TR)] and multidrug resistance-associated protein A (MRPA), and the decreased Sb(III) uptake due to lower level of expression of the gene aquaporin-1 (AQP1) ) may be responsible for the phenotype. Targeted gene expression profiling in Leishmania guyanensis parasites isolated from SAG nonresponsive patients revealed that γ-GCS overexpression is linked with therapeutic failure while ODC and TR were preferentially expressed in nonresponsive Leishmania brazileinsis (Torres et al 2010;Adaui et al 2011). These markers have been studied in very few Indian L. donovani clinical isolates making it difficult to establish correlation with therapeutic response of patients (Mukherjee et al 2007;Mittal et al 2007).…”
Section: Introductionmentioning
confidence: 99%